Reimagining robotic walkers for real-world outdoor play environments with insights from legged robots: a scoping review. - Stewart-Height, Abriana; Koditschek, Daniel E.; Johnson, Michelle J. (Disability & Rehabilitation: Assistive Technology, 2023)
For children with mobility impairments, without cognitive delays, who want to participate in outdoor activities, existing assistive technology (AT) to support their needs is limited. In this review, we investigate the control and design of a selection of robotic walkers while exploring a selection of legged robots to develop solutions that address this gap in robotic AT. We performed a comprehensive literature search from four main databases: PubMed, Google Scholar, Scopus, and IEEE Xplore. The keywords used in the search were the following: "walker", "rollator", "smart walker", "robotic walker", "robotic rollator". Studies were required to discuss the control or design of robotic walkers to be considered. A total of 159 papers were analyzed. From the 159 papers, 127 were excluded since they failed to meet our inclusion criteria. The total number of papers analyzed included publications that utilized the same device, therefore we classified the remaining 32 studies into groups based on the type of robotic walker used. This paper reviewed 15 different types of robotic walkers. The ability of many-legged robots to negotiate and transition between a range of unstructured substrates suggests several avenues of future consideration whose pursuit could benefit robotic AT, particularly regarding the present limitations of wheeled paediatric robotic walkers for children's daily outside use. Children with lower limb disabilities can benefit from assistive technology designed for daily usage in outdoor surroundings. An extension of existing robotic assistive technology that allows the user to travel safely on irregular surfaces both indoors and outdoors is needed. Approaches used to solve research problems in the field of robotics (outside of the rehabilitation area) can be used to address problems that robotic assistive technology currently faces. There is a need for more research on the development of robotic assistive technology for children with mobility impairments without cognitive delays.